Assess, improve, detect, guide: a narrative review and proposal for a standardized protocol for prehospital transesophageal echocardiography during out-of-hospital cardiac arrest - Katzenschlager, Stephan; Hamp, Thomas; Dietrich, Maximilian; Edmunds, Christopher T.; Kaltschmidt, Nikolai; Weigand, Markus A.; Krammel, Mario; Weilbacher, Frank; Popp, Erik (The Ultrasound Journal, 2025)
While there are different protocols for in-hospital transesophageal echocardiography, there is no existing protocol for prehospital usage during out-of-hospital cardiac arrest. Herein, the “assess-improve-detect-guide” protocol is described. This protocol includes four mid-esophageal views to address the most time-sensitive aspects during outof-hospital cardiac arrest. This protocol can be used in services with and without the capability for eCPR, with the benefit of profiting from additional diagnostic and personal resources. This protocol provides a standardized approach for performing transesophageal echocardiography during out-of-hospital cardiac arrest and reporting the results.